2018
DOI: 10.3389/fgene.2018.00135
|View full text |Cite
|
Sign up to set email alerts
|

TIMP3 Overexpression Improves the Sensitivity of Osteosarcoma to Cisplatin by Reducing IL-6 Production

Abstract: Osteosarcoma is the most common bone cancer in children and adolescents. Tissue inhibitors of metalloproteinases (TIMPs)-3 inhibit matrix metalloproteinases to limit extracellular matrix degradation. Cisplatin is a widely used chemotherapeutic drug used to cure osteosarcoma. Interleukin (IL)-6 and TIMP3 play important roles in the drug resistance of osteosarcoma; however, their relationship in this process remains unclear. This study aimed to explore the role of TIMP3 in the cisplatin sensitivity of osteosarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Endogenous IL-6/IL-6-related signaling contribute to elevated proliferation/ chemoresistance of osteosarcoma cells, and induce their epithelial-to-mesenchymal transition (EMT), thus promoting their migration and invasion 20. Furthermore, Han et al reported that osteosarcoma cells become more sensitive to cisplatin when IL-6 production is reduced 21; however, little is known about the relationship between IL-6 expression and the clinicopathological characteristics of patients with osteosarcoma. Moreover, there are no data indicating whether IL-6 can modulate the malignant traits of osteosarcoma, including maintenance/promotion of stemness.…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous IL-6/IL-6-related signaling contribute to elevated proliferation/ chemoresistance of osteosarcoma cells, and induce their epithelial-to-mesenchymal transition (EMT), thus promoting their migration and invasion 20. Furthermore, Han et al reported that osteosarcoma cells become more sensitive to cisplatin when IL-6 production is reduced 21; however, little is known about the relationship between IL-6 expression and the clinicopathological characteristics of patients with osteosarcoma. Moreover, there are no data indicating whether IL-6 can modulate the malignant traits of osteosarcoma, including maintenance/promotion of stemness.…”
Section: Introductionmentioning
confidence: 99%
“…We then generated subcutaneous 143B xenografts in nude mice, and compared the anti-tumor efficiency of F-AgÅPs and cisplatin (a first-line chemotherapeutic drug for osteosarcoma therapy) 32 against osteosarcoma in vivo . Figure 3 A shows the tumor sizes of 143B xenograft-bearing nude mice during an observation period of 21 days after intravenous injection of F-AgÅPs, cisplatin or solvent (normal saline).…”
Section: Resultsmentioning
confidence: 99%
“…TIMP3, a member of the TIMP family, is a 24-kDa secreted glycoprotein and can suppress cell proliferation and enhance chemosensitivity by activating apoptosis-related signal pathways. [33][34][35][36][37] In addition, the analysis of TCGA and CGGA cohorts showed significant negative correlation between MIF and TIMP3 (Figure 5C). Further experiments verified that TIMP3 was upregulated at both mRNA and proteins levels after knockdown of MIF in TR cells (Figures 5D and 5E).…”
Section: Timp3 Is a Downstream Target Of Mif In Glioma Cellsmentioning
confidence: 89%
“…Jackson et al 44 reported that many mechanisms of preventing TIMP3 expression in diverse human cancers support that TIMP3 acts as a tumor suppressor. Han et al 37 reported that TIMP3 overexpression suppressed cell proliferation and enhanced cisplatin sensitivity by activating apoptosis-related signaling pathways. But, so far, the relationship between MIF and TIMP3 has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%